Analisis Perubahan Bilangan Kurva Aliran Permukaan (Runoff Curve Number) Terhadap Debit Banjir Di DAS Lesti - Ideawati, Lenny Febriana; Limantara, Lily Montarcih; Andawayanti, Ussy (Fakultas Teknik, Universitas Brawijaya, 2015)
Land use activities that changing types of land cover, vegetation changes to other vegetation types in managed of natural resources, deforestation, shifting cultivation, and changes in land treatments found in the watershed Lesti. Efforts that can be used as an alternative solution to the landuse change is to analyze the CN (Curve Number) as a variable that classify each landuse, type of soil and vegetation, in order to know the effect of the runoff and river discharge. The study shows CN value increase from 2002 to 2012 an average of 1.03%, average surface runoff 54.79 mm, with an average streamflow of 18.54 m 3 / sec. The changes in land use from 2002 to 2012 caused increase in the value of the CN (Curve Number), surface runoff, and river discharge in Lesti River.Key words: Lesti Watershed, Curve Number, Runoff